Numerical Simulation of Residual Stresses and Distortions in Butt Weld in Simulation Programme Sysweld - Radoslav Konar; Milos Mician (Communications, 2012)
The article describes the theoretical knowledge of the residual stresses induced during welding in butt welded joint and the possibilities of their simulations in a simulation programme SYSWELD. In conclusion are compared experimental and simulated results.